Formulation and Evaluation of Sappan Wood Extract Transparent Solid Soap with Variations in the Concentration of Glycerin as a Humectant - Yusuf Supriadi; Bekti Dwi Cahyani (The Indonesian Institute of Science and Technology Research, 2022)
Soap is a product that can be used to clean hands from bacteria and dirt. One of the natural ingredients that can be formulated into soap is sappan wood. Sappan wood contains 5 compounds belonging to flavonoids, including brazilin, brazilein, 3'-O-methyl brazilin, sappanin, chalcone, and sappanchalcone which have antioxidant and antibacterial properties. This study aims to formulate sappan wood extract into a transparent solid soap preparation with an olive oil base using variations in glycerin concentration, namely F1 (10%), F2 (15%), and F3 (20%) transparent soap preparations. The type of research conducted is experimental research. Evaluation of transparent soap preparations consisted of organoleptic testing, pH, moisture content, foam stability, wetting power, and hardness of the preparation. The results of the study showed that the transparent soap met the requirements for the organoleptic test, pH test, water content test, wetting power test, and hardness test. In the results of the stability test, F3 foam has a longer foam stability compared to F1 and F2.